An Origenian Background for the Letter to Theodore - Zeddies, Michael T. (Harvard theological review, 2019)
The Letter to Theodore may need to be reattributed to Origen of Alexandria. Many of its features seem demonstrably Origenian, and its language aligns with early Christian and Origenian usage. Two noncanonical gospel fragments in the letter do not betray a modern author, but rather evoke early Christian symbolism and narrative structure. The single garment worn by a character in the first fragment reflects Christian symbolism and resembles the philosopher's garment, which many early Christians adopted and portrayed in material artifacts. Origen's intellectual interests can explain the letter's preparation for philosophical exegesis, and its language reflects his text-critical practice. Nevertheless, Origen's circumstances indicate the text of the noncanonical gospel fragments is unreliable. The letter also echoes Papias in the manner that Origen does. Morton Smith's account of its discovery does not betray a forgery or hoax, but plausibly depends on other nonfiction works of manuscript discoveries written during the 1960s. Further work may be needed to secure attribution, but Origenian authorship is a simpler explanation of the evidence than modern forgery.